(untitled) (Sociologisk Forskning, 1998)
The problem of how to relate to previous research in the research process is severe when normal science has not been established, e.g. as in the case of sociology and as in certain fields of inter-disciplinary research. Yet, this problem has been more or less neglected in methodological textbooks. Under non-normal circumstances the reasoning is often very complex and it may be difficult to determine which literature is relevant to relate to and how this should be done. Thus, an explicit and systematic strategy is needed to make the problem more comprehensible. It is argued that argument analysis (cf. critical thinking) can serve this purpose. In addition, a hypothesis concerning the importance of the cognitive dimension in soft sciences is outlined.